When does obesity exert its effect in conferring risk of developing RA: a large study in cohorts of symptomatic persons at risk - Hanna W van Steenbergen; Pascal H P de Jong; Elise van Mulligen; A Willemze; Quirine A Dumoulin; Doortje I Krijbolder; Anna M P Boeren; Annette H M van der Helm - van Mil (RMD Open)
Objectives Obesity is a known risk factor for developing rheumatoid arthritis (RA). However, it is unclear whether obesity exerts its risk effect during the asymptomatic or the symptomatic clinically suspect arthralgia (CSA) phase of risk. To improve understanding of the effect of obesity on RA development, we aimed to (1) compare body mass index (BMI) at CSA onset to BMI of the general population and (2) study within CSA patients if obesity increases the risk for progression to RA.Methods 1107 symptomatic persons at risk for RA from four cohorts (CSA Leiden, CSA Rotterdam, SONAR and TREAT EARLIER placebo arm) were studied. For the first aim, baseline BMI was compared with age-matched/sex-matched BMI of the general population. Patients were stratified for anticitrullinated protein antibody (ACPA) status. Regarding the second aim, the association between BMI and inflammatory arthritis (IA) development during 2 years was studied with Cox regression analysis within each cohort and via meta-analysis in all cohorts.Results CSA patients of all cohorts were more often obese than the general population (respectively 21.9% vs 14.0%, 25.7% vs 14.5%, 26.7% vs 14.5% and 33.3% vs 14.9%, in CSA Leiden, CSA Rotterdam, SONAR, TREAT EARLIER placebo arm). Both ACPA-positive and ACPA-negative CSA patients had a higher frequency of obesity. Within CSA, obesity was not associated with IA development compared to normal weight (pooled effect in meta-analysis of four cohorts HR 1.01 (95% CI 0.93 to 1.08)).Conclusions Obesity is not associated with RA development within CSA patients but BMI has already increased in CSA compared to the general population. Obesity, therefore, presumably exerts its risk effect at an early asymptomatic phase of RA development, rather than being associated with the disease processes that ultimately result in clinical arthritis.